The Effects of Age and Number of Grafted Larvae on Some Physical Characteristics of Queen Bees and Acceptance Rate of Queen Bee Cell - Samet Okuyan; Ethem Akyol (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out to determine the effects of age and number of grafted larvae on acceptance rates, body weight, body length, head width and length, thorax width and length, and wing width and length of queen bees. One breeding and eleven starter hives were used for rearing queen bees. Totally, 495 one, two, and three-day-old larvae were grafted into starter hives comprising 30, 45, and 60 and 414 larvae were accepted; thus, generally, the acceptance rate was calculated as 83%. The best acceptance rate was calculated in three-day-old larvae group as 85.15%. There were found a statistically significant effect of the number of grafted larvae on body length and head width of queen. However, there were any effects on weight, head length, thorax width, thorax length, wing width, wing length, and acceptance rate of larvae. Age of grafted larvae did not have a statistically significant effect on head width, head length, wing width and acceptance rate of larvae. On the other hand, age of grafted larvae had a statistically significant effect on queen weight, body length, thorax width and length, and wing length of queen. If bee breeders wish to improve their stock, they should graft one-day-old larvae for rearing better queen bees.